Association of polymorphism at Exon-1 of the alpha 1-antitrypsin gene with milk production traits in Sahiwal and Karan Fries Cattle - Yadav, Alok Kumar; Mukherjee, Anupama (Indian Journal of Dairy Science, 2019)
PCR-RFLP analysis of PCR products were carried out using Sph I /Pae1enzyme for 100 Sahiwal cattle and 115 Karan Fries animals. In Sahiwal cattle the 448 bp have three genotype AA (448), AB (448+313+135bp), BB (313+135 bp) having genotype frequencies 0.20, 0.45, 0.35 and gene frequencies are 0.42 (A) and 0.58 (B) and in Karan Fries cattle genotype frequencies 0.29, 0.21, 0.50 respectively and gene frequencies are 0.39 (A) and 0.61 (B). These genotypes of 448 bp are highly significant for FL305DMY, FLTMY, FL305DSNFY and non significant for FL305 DFY and FL305DPY in Sahiwal and In Karan Fries cattle these genotypes are highly significant for FL305DMY, FLTMY, FL305DSNFY and FL305DPY and non significant for FL305DFY. AB genotype was superior for FL305DMY, FLTMY, FL305DSNFY traits and AA genotype was superior for FL305DFY and BB genotype was superior for FL305DPY trait in Sahiwal cattle and In Karan Fries Cattle AB genotype was superior for all traits.